Kazenska odgovornost učitelja v zvezi z nasiljem v šoli - Korošec, Damjan (Pravni letopis, 2009)
It is important to understand, that a teacher as perpetrator of criminal acts in school can be criminal liable for commissions, for omissions and for commissions by omissions. On the level of theory of substantive criminal law, legal norms as well as several examples from the praxis of Slovenian schools the author shows the main differences between these categories of crimes, including interesting special problems of pseudo-causality in omissions and analyzes several incriminations of violent conduct in the Slovenian Criminal Code (KZ-1, Official Journal of the Republic of Slovenia, Nr. 55/08, 66/08, 39/09), where the teacher can be held liable, all with special focus on commissions by omission. The goal of the article is to show the teacher how to avoid not only violent acts in schools, but also his own criminal liability for violent acts in school.
Keywords: criminal law; kazenska odgovornost; kazensko pravo; nasilje; Slovenia; Slovenija; šole; učitelji